Determinants of and barriers to adoption of digital therapeutics for mental health at scale in the NHS. Issue 3 (7th May 2020) - Williams, Matt G; Stott, Richard; Bromwich, Nicki; Oblak, Susie K; Espie, Colin A; Rose, James B
Abstract : Objectives: Although it is widely acknowledged that digital therapeutics will play a significant role in the future delivery of healthcare, the method by which these innovations may be commissioned by the National Health Service, at scale, remains unclear. This study explores English health commissioners' experiences of, and attitudes towards, adopting digital healthcare innovations. Methods: 37 commissioners and decision-makers from a range of sectors within the health profession were invited to participate in structured interviews to gather relevant examples of experience and opinions. 14 commissioners participated and the notes from the resulting interviews were interpreted using qualitative content analysis. Controlled interpretation was applied to the categorised responses, paraphrasing and classifying into themes. Results: Common determinants and barriers to adoption of digital mental health expressed during the interview process included commissioners' lack of familiarity with technology, information governance, digital literacy of users and decision-makers. Conclusions: Recognition of identified barriers may be helpful for innovators when developing engagement and market access strategies and suggest areas for focus and further development within the commissioning process to accommodate digital health solutions.